2018
DOI: 10.1093/database/bay027
|View full text |Cite
|
Sign up to set email alerts
|

Maser: one-stop platform for NGS big data from analysis to visualization

Abstract: A major challenge in analyzing the data from high-throughput next-generation sequencing (NGS) is how to handle the huge amounts of data and variety of NGS tools and visualize the resultant outputs. To address these issues, we developed a cloud-based data analysis platform, Maser (Management and Analysis System for Enormous Reads), and an original genome browser, Genome Explorer (GE). Maser enables users to manage up to 2 terabytes of data to conduct analyses with easy graphical user interface operations and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…The sequence data were deposited in the DNA Data Bank Japan Sequence Read Archive (accession numbers are shown in Supplementary file 1). The raw reads were subjected to de novo assembly using the Trinity program (Grabherr et al, 2011) implemented in the MASER pipeline (Kinjo et al, 2018). After automatic assembling, we checked and manually corrected the sequences of genes that are highly expressed in mature males using the Integrative Genomics Viewer (Thorvaldsdóttir et al, 2013) as reported previously (Futahashi, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The sequence data were deposited in the DNA Data Bank Japan Sequence Read Archive (accession numbers are shown in Supplementary file 1). The raw reads were subjected to de novo assembly using the Trinity program (Grabherr et al, 2011) implemented in the MASER pipeline (Kinjo et al, 2018). After automatic assembling, we checked and manually corrected the sequences of genes that are highly expressed in mature males using the Integrative Genomics Viewer (Thorvaldsdóttir et al, 2013) as reported previously (Futahashi, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The dataset was downloaded and edited by the FASTX‐TOOLKIT 0.0.13 software. The de novo transcriptome assembly was implemented using Trinity software in the MASER pipeline . The nucleotide sequences were translated by the TransDecoder v.5.3.0 tool.…”
Section: Methodsmentioning
confidence: 99%
“…The transposon sequence analysis was analyzed using BLAST program with TREP database [14] (data file 8, data file 9). Transcriptome reference was assessed using Busco v.3.2 [15] under Maser platform [16] (data file 10). The SwissProt-annotated contigs were used to analyze GO and KEGG pathways using Blast2GO 5.2 (data file 11).…”
Section: Data Descriptionmentioning
confidence: 99%